1995
DOI: 10.1103/physreva.52.1775
|View full text |Cite
|
Sign up to set email alerts
|

Electron correlation in double photoionization: Comparative study of secondary structure for Ne and Xe

Abstract: The extended Wannier ridge model is shown to be able to reproduce the observed triple differential cross sections (TDCS) for the double-photoionization process y+Ne(2p ) -+Ne +(2p 'S')+e+e at a rather high excess energy E=40.6 eV. The secondary maximum in TDCS is related to the kinematic electron correlation in the initial state just as in the previously studied photoionization of Xe atoms. Variation of TDCS patterns at varying energies for Ne and Xe atom is described.PACS number(s): 32.80. Fb, 34.80.Dp, 34.80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 11 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…Kazansky and Ostrovsky [15] have shown that the relative intensity of the secondary structure in Xe is quite sensitive to the degree of initial-state correlation. On the other hand, the same model predicted TDCS in reasonable agreement with the Ne data discussed above [10][11][12] employing uncorrelated initial-state wave functions [16].…”
Section: Introductionsupporting
confidence: 70%
“…Kazansky and Ostrovsky [15] have shown that the relative intensity of the secondary structure in Xe is quite sensitive to the degree of initial-state correlation. On the other hand, the same model predicted TDCS in reasonable agreement with the Ne data discussed above [10][11][12] employing uncorrelated initial-state wave functions [16].…”
Section: Introductionsupporting
confidence: 70%
“…This result can be established from very general considerations [1,2], and was first derived in the context of the 'Wannier' theory by Huetz et al [3]. The validity of this form has been confirmed not only by the fitting of a large body of experimental data but also by the success of ab initio calculations using a variety of approaches to represent the three-body Coulomb final state [4][5][6]8].…”
Section: Introductionmentioning
confidence: 73%
“…For increasing k the angular variation shows an increasing number of nodes. Finally, in figure 4 the angular distribution in the laboratory frame, given by T el f i 2 of equation (8), is shown for an energy of 10 eV and various orientations of R with respect to ˆ . At this energy, one notes only a slight dependence upon the orientation of the nuclear axis consistent with figure 3.…”
Section: Photoionization Of H +mentioning
confidence: 99%
“…In cold plasmas, the strong quasistatic fields [20] between the (almost stationary) positive ions and the electrons cause complete -mixing within n-shells. The field-induced population and depopulation of various -levels [21,22], with their radically different lifetimes, have been implicated in various cross-section [23][24][25] and stability-related phenomena in dilute plasmas [26,27]. The complete symmetry breaking under the influence of the electric and magnetic fields is reminiscent of the crossedfields problem with arbitrary orientations [28,29] except that the zero-order symmetry here is closer to the cylindrical symmetry of the TCC than to the hydrogen atom.…”
Section: Introductionmentioning
confidence: 99%